The burden of hepatitis E virus infection among Ghanaian pregnant women - Husein Bagulo; Husein Bagulo; Ayodele O. Majekodunmi; Ayodele O. Majekodunmi; Susan C. Welburn; Susan C. Welburn; Langbong Bimi (Frontiers in Public Health)
IntroductionHepatitis E virus (HEV) infection poses a significant burden on pregnant women, with associated negative outcomes. Although well-described in many developed countries, the epidemiology of the disease and its impact on maternal and fetal health in Ghana is not fully understood.Materials and methodsA cross-sectional survey was conducted in the antenatal clinics of 10 district hospitals in five regions of Ghana. The study involved 1,000 pregnant women attending antenatal care. Serological and virological assays were employed to determine HEV seroprevalence and prevalence. Logistic regression analysis was carried out in univariate and multivariate models to assess risk factors associated with HEV infection.ResultsHEV-Immunoglobulin G (IgG) seroprevalence of 8.3% was recorded among the pregnant women with 1% HEV-antigen prevalence. However, none were positive for HEV-IgM and HEV RNA. 19.8% of the pregnant women reported poor pregnancy outcomes in previous pregnancies. Age, educational attainment, and region were significant predictors of HEV IgG seropositivity in the univariate regression model, while age and region were the only significant predictors in a multivariate model. Also, the drinking water source and the toilet type accurately predicted HEV IgG seroprevalence in both univariate and multivariate models.DiscussionPregnancy care must be significantly improved to reduce maternal and foetal morbidity and mortality.